Loisaida as urban laboratory: pioneering community activism in New York, 1964–2001 - Schrader, Timo (2018)
This thesis offers the first in-depth analysis of the network of Puerto Rican community activism in the Lower East Side from 1964 to 2001. The community of Loisaida organized itself to fight against postwar urban deindustrialization, housing disinvestment, and gentrification, which threatened to displace an entire generation of Puerto Ricans who migrated to this New York neighborhood and tried to make it their home. Using an amalgam of unprocessed organizational archives, oral histories, ephemera, and neighborhood publications, this project recreates the history of community action in Loisaida. Focusing on key institutions and community groups that mobilized residents and built a lasting activist network, this thesis demonstrates how community groups pioneered a methodology for more sustainable community activism. These activists turned Loisaida into their laboratory, constantly experimenting with and adapting new strategies to put up a solid defense against absentee landlords, greedy developers, opportunist politicians, and an era of increased policing of urban space.